2021
DOI: 10.1111/ger.12605
|View full text |Cite
|
Sign up to set email alerts
|

Association between dry mouth and physical frailty among community‐dwelling older adults in Japan: The Otassha Study

Abstract: Objective To elucidate the relationship between physical frailty and dry mouth among community‐dwelling older adults in Japan. Background Oral hypofunction is associated with physical frailty in older adults. Dry mouth, subjectively evaluated as xerostomia and objectively measured as hyposalivation, is highly prevalent in older adults. However, few reports have used both measures of dry mouth and investigated their association with physical frailty. Materials and Methods This cross‐sectional study included 643… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
4
4
0
Order By: Relevance
“…[19][20][21][22][23] Moreover, saliva plays various roles in maintaining oral health, food intake and preventing oral diseases. [24][25][26] A previous study showed that self-reported assessment of dry mouth was more useful than objective assessment, which is consistent with our findings. 24 Recovery to robust status was associated with a "No" response to "In the last 2 weeks have Frailty in older adults and COVID-19…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…[19][20][21][22][23] Moreover, saliva plays various roles in maintaining oral health, food intake and preventing oral diseases. [24][25][26] A previous study showed that self-reported assessment of dry mouth was more useful than objective assessment, which is consistent with our findings. 24 Recovery to robust status was associated with a "No" response to "In the last 2 weeks have Frailty in older adults and COVID-19…”
Section: Discussionsupporting
confidence: 93%
“… 24 , 25 , 26 A previous study showed that self‐reported assessment of dry mouth was more useful than objective assessment, which is consistent with our findings. 24 Recovery to robust status was associated with a “No” response to “In the last 2 weeks have you felt a lack of fulfillment in your daily life?”. Participating in hobbies is fulfilling and can improve the quality of life and self‐rated health.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Salivary flow reduction is not necessarily associated with the subjective feeling of dry mouth and other xerostomia problems [ 21 ]. Ohara et al showed that although no difference was observed between hyposalivation and the severity of physical frailty, xerostomia is associated with physical frailty, which is defined as having three or more components of weakness, slowness, weight loss, low physical activity level, or exhaustion among older adults adjusted for demographic and health characteristics [ 48 ]. Older patients perceived that their xerostomia and OHRQoL improved after receiving new removable partial or complete dentures [ 9 ].…”
Section: Discussionmentioning
confidence: 99%